Thiobarbituric acid-reactive substances relate to arterial stiffness and blood pressure in 6 to 8-year-old boys stratified by maternal risk. (1st February 2018) - Craig, Ashleigh; Mels, Catharina M. C.; Kruger, Ruan
Abstract: Early cardiovascular disease (CVD) onset can be inflicted by familial cardiovascular and lifestyle risk factors. We aimed to compare phenotypic characteristics and explore associations between oxidative stress and vascular function in boys stratified by maternal cardiovascular and lifestyle risk. We included 40 Black and 41 White boys (ages 6–8 years), along with the biological mother of each child. The study population was divided into two groups (nonmaternal risk vs. maternal risk) according to maternal risk predetermined by their selfreported cardiovascular and lifestyle risk factors. Pulse wave velocity (PWV) was measured at various sites and blood pressures were recorded. Urine samples were collected for analyses of thiobarbituric acid-reactive substances (TBARS), 8-hydroxy-2-deoxy guanosine (8-OHdG), albumin, and creatinine. Higher levels of urinary albumin to creatinine ratio (uACR) were found in the maternal risk group compared to the nonmaternal risk group ( p = .038). Multiple regression analysis in the maternal risk group revealed diastolic blood pressure ( R 2 = 0.159; β = 0.293; p = .050), carotid femoral PWV ( R 2 = 0.158; β = 0.297; p = .038) and carotid dorsalis pedis PWV (adj R 2 = 0.322; β = 0.505; p < .001) to be positively associated with TBARS, while an inverse association of uACR ( R 2 = 0.161; β = −0.261; p = .046) with TBARS was observed. Also, in the maternal risk group, independent associations of DBP ( R 2 = 0.273; β = 0.289; p = .040) and uACR ( R 2 = 0.283; β = 0.268; p = .027) with 8-OHdG were indicated. In boys, as young as 6 years of age, oxidative stress related to arterial stiffness and diastolic blood pressure was observed. This association was only evident in boys with linked maternal lifestyle and cardiovascular risk factors, suggesting potential family-related early onset of cardiovascular risk.